The genus Akodon (Muroidea: Sigmodontinae) in Misiones, Argentina - Pardiñas, Ulyses Francisco José (2003)
Our understanding of the rodent diversity from the Argentinean Atlantic rainforest and its surrounding environments (Misiones Province) is still relatively poor. Here we present an update on the species inhabiting Misiones of the genus Akodon. Integrated analyses of morphology, chromosomal and molecular data allow us to document the existence of four species of Akodon in the province. One of these is apparently undescribed, and is known only from one locality in the ‘campos’ phytogeographic unit of southern Misiones. A second species, A. montensis, has a large distribution and is one of the dominant sigmodontine species in primary and secondary forest. Akodon sp. 2, previously reported as either A. serrensis and A. paranaensis, is known from only one locality at the northeast of the province, where it is sympatric with A. montensis. Also in sympatry with A. montensis at one locality in central Misiones there is a similar species with a gall bladder referred here to A. cursor. Finally, the previous reference of one specimen to A. serrensis must be discarded due to the referred specimen is lost, and the data at hand are insufficient to corroborate the identity of the specimen under question. As Misiones has the largest continuous patches of southern interior Atlantic rainforest remaining in Argentina we pose comments on the conservation significance of our study.